2023
DOI: 10.1186/s44149-022-00064-6
|View full text |Cite
|
Sign up to set email alerts
|

First molecular identification of multiple tick-borne pathogens in livestock within Kassena-Nankana, Ghana

Abstract: The risk of pathogen transmission continues to increase significantly in the presence of tick vectors due to the trade of livestock across countries. In Ghana, there is a lack of data on the incidence of tick-borne pathogens that are of zoonotic and veterinary importance. This study, therefore, aimed to determine the prevalence of such pathogens in livestock using molecular approaches. A total of 276 dry blood spots were collected from cattle (100), sheep (95) and goats (81) in the Kassena-Nankana Districts. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 122 publications
0
1
0
Order By: Relevance
“…These benefits include noninvasive blood collection, reduced blood volume needed, ease of transport, and long-term blood spot storage [ 22 , 23 ]. Research has successfully identified tick-borne diseases in livestock DBSs [ 24 26 ]. This study sought to determine the tick-borne pathogens in slaughtered livestock and abattoir workers in Kumasi.…”
Section: Introductionmentioning
confidence: 99%
“…These benefits include noninvasive blood collection, reduced blood volume needed, ease of transport, and long-term blood spot storage [ 22 , 23 ]. Research has successfully identified tick-borne diseases in livestock DBSs [ 24 26 ]. This study sought to determine the tick-borne pathogens in slaughtered livestock and abattoir workers in Kumasi.…”
Section: Introductionmentioning
confidence: 99%